Composite material liner and production process thereof

Through the composite processes of plasma activation, ultraviolet modification, laser etching and nanocoating treatment, the problem of insufficient processing accuracy of the surface structure of composite material pads is solved, and high-strength and durable composite material pads are realized, improving its performance and applicability in the electronic equipment, automotive interior and packaging industries.

CN120481314AActive Publication Date: 2025-08-15DONGGUAN LONGJIA NEW MATERIALS TECHNOLOGY CO LTD

Patent Information

Application Number
CN202510675484.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-23
Publication Date
2025-08-15
Estimated Expiration
2045-05-23

AI Technical Summary

Technical Problem

The surface structure processing accuracy in the existing composite material liner production process is insufficient, resulting in inconsistent mechanical properties of the liner and insufficient adhesion of the coating, affecting its application in electronic equipment, automotive interiors and packaging industries.

Method used

Plasma surface activation treatment and ultraviolet radiation modification composite treatment are used to form a groove network structure with a laser, and nanocoating spraying and hot pressing are carried out, and the precise size is finally achieved through laser cutting.

Benefits of technology

It significantly improves the mechanical properties and coating adhesion of composite material pads, and improves the applicability and reliability of the products in the electronic equipment, automotive interiors and packaging industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120481314A_ABST
    Figure CN120481314A_ABST
Patent Text Reader

Abstract

The invention discloses a composite material liner and a production process thereof, and the production process comprises the following steps: carrying out plasma surface activation treatment on a foam substrate to obtain an activated foam substrate; the activated foam substrate and a polyester film are placed in ultraviolet irradiation equipment to be subjected to modified composite treatment, and a composite base material is obtained; performing line-by-line irradiation on the composite base material along a preset grid pattern based on a laser, forming a groove network structure on the surface of the composite base material, and obtaining a grid base material with grid identification lines; the grid base material is subjected to nanometer coating spraying treatment, and a coating base material is obtained; the coating base material is subjected to hot-pressing shaping treatment, and a semi-finished liner product is obtained; and the semi-finished liner is subjected to laser cutting treatment according to the preset size, and the composite liner is obtained. Through the integrated process design, the technical bottleneck that in the prior art, the surface structure machining precision is insufficient is remarkably overcome, and the applicability and reliability of the product in the electronic equipment industry, the automotive trim industry and the packaging industry are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of composite material gaskets, and in particular to a composite material gasket and a production process thereof. Background Art

[0002] Composite gaskets offer excellent cushioning, flexibility, and durability, and are widely used in electronic devices, automotive interiors, and the packaging industry. Currently, composite gaskets are produced by combining a foam base with a functional film (such as polyethylene or polypropylene film) to enhance the gasket's mechanical properties or surface characteristics.

[0003] The main technical defects of the existing composite material gasket production process are concentrated on the lack of accuracy and consistency in surface structure processing. During the manufacturing process, in order to improve the flexibility, air permeability or interlocking ability of the gasket with other components, it is often necessary to form a specific pattern or groove structure on the surface of the composite substrate. However, existing methods such as mechanical embossing or manual cutting can easily lead to uneven surface patterns, rough edges or damage to the internal structure of the material during processing. This lack of processing accuracy directly affects the mechanical properties of the gasket, such as fluctuations in tensile strength or fatigue resistance, especially under high load or long-term use scenarios. In addition, the application of surface functional coatings is usually separated from surface structuring, and the coating is difficult to fully combine with irregular surfaces, resulting in insufficient adhesion or peeling during use. The lack of surface structure processing accuracy has become a key technical bottleneck that limits the performance and application range of composite material gaskets.

[0004] Therefore, a new production process is urgently needed to overcome the limitations of existing technologies in surface structure processing accuracy through integrated process design, and to achieve composite material liners with consistent performance and precise structure. Summary of the Invention

[0005] The purpose of this application is to provide a composite material liner and its production process to solve the technical problem of insufficient surface structure processing precision of existing composite material liners. To achieve this goal, this application adopts the following technical solutions: A production process for a composite material liner, comprising: performing plasma surface activation treatment on the foam substrate to obtain an activated foam substrate; placing the activated foam substrate and the polyester film in an ultraviolet irradiation device for modification and composite treatment to obtain a composite substrate; Based on the laser irradiation on the composite substrate line by line along a preset grid pattern, a groove network structure is formed on the surface of the composite substrate to obtain a grid substrate with grid identification lines; performing nano-coating spraying treatment on the grid substrate to obtain a coating substrate; Performing hot pressing and shaping treatment on the coating substrate to obtain a semi-finished gasket product; The semi-finished gasket is laser cut according to a preset size to obtain a composite gasket.

[0006] Furthermore, the polyester film is a combination of one or more of PET film, PBT film and PEN film.

[0007] Furthermore, the step of subjecting the foam substrate to plasma surface activation treatment to obtain an activated foam substrate comprises: placing the polyurethane foam substrate in an ultrasonic cleaning device, and using a mixed solution of deionized water and isopropyl alcohol as a cleaning medium to clean the polyurethane foam substrate to obtain a foam substrate; The foam substrate is placed in a low-pressure plasma treatment chamber, and a mixed gas of argon and nitrogen is introduced, with the volume ratio of argon to nitrogen controlled to be 3:1 and the power set to 200 W to obtain a primary activated substrate; The gas was exhausted and a mixed gas of oxygen and carbon tetrafluoride was introduced, the volume ratio of oxygen to carbon tetrafluoride was controlled to be 4:1, and the power was set to change periodically between 250W and 350W to obtain an activated foam base.

[0008] Furthermore, the step of placing the activated foam substrate and the polyester film in an ultraviolet irradiation device for modification and composite treatment to obtain a composite substrate includes: A mixed solution of acrylate prepolymer containing a photoinitiator and nano zinc oxide particles in propylene is coated on the surface of the polyester film, and pre-cured under the protection of an inert gas to obtain an initial polyester film; The initial polyester film is placed in an ultraviolet irradiation device for modification treatment, the ultraviolet light source of the device is set to have a wavelength of 355-365 nm and an irradiation intensity of 100-150 mW / cm², to obtain a modified polyester film; Applying an environmentally friendly polyurethane hot melt adhesive on the surface of the activated foam base, and flattening the surface with a cooling roller to obtain an adhesive foam base; The modified polyester film and the adhesive foam substrate are subjected to hot melt lamination treatment at a lamination temperature of 120-140° C. and a lamination time of 30-60 seconds to form a composite substrate.

[0009] Furthermore, the step of irradiating the composite substrate line by line along a preset grid pattern with a laser to form a groove network structure on the surface of the composite substrate to obtain a grid substrate with grid identification lines includes: Collecting first surface topography data of the composite substrate using a computer device, and generating a laser irradiation path based on the first surface topography data, wherein the laser irradiation path includes intersecting lines in different directions and a varying area of a preset depth; performing incident irradiation treatment on the composite substrate at multiple angles according to the laser irradiation path to form a primary network substrate, wherein the intersection of the multiple angles forms a varying region of the preset depth; collecting second surface topography data of the primary network substrate, and optimizing the curvature of the intersection according to the second surface topography data to form an optimized curvature parameter; performing a secondary laser irradiation process on the primary network substrate according to the optimized curvature parameters to form an optimized network substrate; The inner wall of the groove on the optimized network substrate is etched based on a laser, and the edge of the inner wall of the groove is locally melted to obtain a grid substrate with grid identification lines.

[0010] Furthermore, the step of performing a secondary laser irradiation treatment on the primary network substrate according to the optimized curvature parameters to form an optimized network substrate includes: Dividing the surface of the primary network substrate into a plurality of energy partitions according to the second surface topography data of the primary network substrate and the optimized curvature parameter; A corresponding laser power is set for each of the energy partitions, and the primary network substrate is irradiated according to the laser power to obtain the optimized network substrate.

[0011] Furthermore, the step of spraying the mesh substrate with a nano-coating to obtain a coated substrate comprises: Spraying a composite solution containing nano-titanium dioxide, a silane coupling agent, and a polyurethane resin onto the surface of the mesh substrate to form a primary-coated mesh substrate, wherein, calculated by mass ratio, titanium dioxide accounts for 6-8%, the silane coupling agent accounts for 2-3%, and the remainder is the polyurethane resin; The pre-coated mesh substrate is placed in a reaction kettle and cured at a low temperature of 50-60° C. for 1.5-2 hours to obtain a cured mesh substrate; A polishing liquid containing nano-alumina particles is applied to the surface of the solidified grid substrate, and the solidified grid substrate coated with the polishing liquid is polished using a polishing device to obtain a coated substrate, wherein the alumina particles have a size of 50-80 nm and the polishing pressure is 0.1-0.15 MPa.

[0012] Furthermore, the step of performing hot pressing and shaping treatment on the coating substrate to obtain a semi-finished gasket product includes: placing the coating substrate in a reaction kettle, and performing a preheating softening treatment on the coating substrate at a temperature of 120-130° C. to obtain a preheated substrate; spraying a fluorinated non-stick coating onto the surface of a pre-shaping mold, placing the preheated substrate in the pre-shaping mold, and performing a pre-shaping treatment on the preheated substrate at 0.5-1 MPa to obtain a pre-shaping substrate; Transferring the pre-shaped substrate to a high-temperature and high-pressure hot press for high-temperature and high-pressure shaping treatment to obtain a shaped substrate, wherein the hot pressing temperature is set at 160-180° C. and the pressure is set at 2.5-3.5 MPa; The shaped substrate is subjected to a gradient cooling treatment, in the first stage the temperature is reduced from 180°C to 100°C with a cooling rate controlled at 5°C / min, and in the second stage the temperature is reduced from 100°C to 50°C with a cooling rate slowed to 35°C / min, to obtain a semi-finished gasket product.

[0013] Furthermore, the step of laser cutting the semi-finished gasket according to a preset size to obtain a composite gasket includes: Laser cutting the semi-finished gasket product according to a preset profile using a multi-wavelength laser to obtain a cut substrate, wherein the short-wavelength laser corresponds to the polyester film layer and the long-wavelength laser corresponds to the foam base; Obtaining the integrity of the marking line on the surface of the cut substrate using an optical inspection device, and determining whether the cut substrate meets the preset size requirements; If not, the cut substrate is corrected until it meets the preset size requirements to obtain a composite material liner.

[0014] The present application also discloses a composite material liner, which is produced using the production process of a composite material liner as described in any one of the above items.

[0015] Compared with the prior art, this application has the following beneficial effects: The present application discloses a production process for a composite material gasket, which achieves high-strength molecular-level bonding between the foam base and the polyester film through plasma surface activation treatment and ultraviolet irradiation modification composite treatment, thereby improving the mechanical properties of the composite substrate, such as tensile strength and fatigue resistance. The groove network structure is formed by laser irradiation row by row along a preset grid pattern, which has extremely high processing accuracy and consistency. The edges of the grid identification lines are smooth and the patterns are regular, which solves the problems of surface unevenness and material damage caused by mechanical embossing or manual cutting, and significantly enhances the flexibility of the gasket and its ability to fit with other components. The coordinated design of the nano-coating spray treatment and the groove network structure enables the coating to adhere evenly to complex surfaces, significantly improving the adhesion and durability of the coating and effectively preventing the occurrence of peeling.

[0016] In summary, the production process of the present invention achieves a composite material liner with consistent performance, precise structure and durability through the organic integration of various steps, significantly improving the applicability and reliability of the product in the electronic equipment, automotive interior and packaging industries. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are only some embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying any creative labor.

[0018] The structures, proportions, sizes, etc. depicted in the drawings of this specification are only used to match the contents disclosed in the specification so as to facilitate understanding and reading by persons familiar with this technology. They are not intended to limit the conditions under which this application can be implemented, and therefore have no substantive technical significance. Any structural modifications, changes in proportional relationships, or adjustments in size, without affecting the efficacy and objectives that can be achieved by this application, should still fall within the scope of the technical contents disclosed in this application.

[0019] Figure 1 Schematic diagram of the overall steps of the production process of a composite material liner. DETAILED DESCRIPTION

[0020] In order to make the purpose, features, and advantages of the invention of this application more obvious and easy to understand, the technical solutions in the embodiments of this application will be clearly and completely described below in conjunction with the drawings in the embodiments of this application. Obviously, the embodiments described below are only part of the embodiments of this application, not all of the embodiments. Based on the embodiments in this application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0021] In the description of this application, it should be understood that the terms "upper", "lower", "top", "bottom", "inner", "outer", etc., indicating orientations or positional relationships, are based on the orientations or positional relationships shown in the accompanying drawings and are intended only to facilitate the description of this application and simplify the description. They do not indicate or imply that the devices or elements referred to must have a specific orientation, be constructed and operate in a specific orientation, and therefore should not be understood as limiting this application. It should be noted that when a component is considered to be "connected" to another component, it may be directly connected to the other component or there may be a centrally located component.

[0022] The technical solution of the present application will be further explained below with reference to the accompanying drawings and through specific implementation methods.

[0023] refer to Figure 1 , the present application provides a production process for a composite material liner, comprising: S1: performing plasma surface activation treatment on the foam substrate to obtain an activated foam substrate; In step S1, a foam base material is selected. Polyurethane foam with a thickness of 2-5 mm can be used as the initial material. This thickness range balances the lightweight and structural strength of the lining. Plasma surface activation treatment, through the bombardment of high-energy plasma, introduces reactive groups onto the foam surface and optimizes the surface microstructure, thereby increasing surface energy and hydrophilicity. In practice, plasma surface activation treatment is performed in a low-pressure plasma chamber. The polyurethane foam is placed in a plasma treatment chamber using a mixed atmosphere of argon and oxygen. The pressure is controlled within the range of 50-100 Pa to ensure plasma stability and uniformity. The argon gas primarily acts as a physical bombardment in the plasma, lightly etching the foam surface and increasing surface roughness. After 10 minutes, the oxygen gas chemically promotes the breaking of surface chemical bonds and the generation of reactive groups. During the treatment process, the equipment power is set to 100-200 W, and the treatment time is controlled to 3-5 minutes to avoid surface damage caused by excessive treatment. The high-energy electrons, ions, and free radicals in the plasma interact with the molecules on the foam surface, breaking carbon-hydrogen bonds and introducing oxygen-containing functional groups such as hydroxyl (-OH) and carboxyl (-COOH). These active groups significantly increase the polarity and chemical activity of the surface, increasing the surface energy from an initial 30 mN / m to over 50 mN / m. At the same time, the surface contact angle is significantly reduced, indicating a significant increase in hydrophilicity. In addition, plasma treatment can effectively remove oil and impurities from the foam surface, further cleaning the surface and increasing the micro-roughness. This increase in roughness further enhances the bonding strength with the polyester film through mechanical intercalation. It should be noted that the parameters of the plasma treatment need to be optimized according to the specific characteristics of the foam substrate and the subsequent process requirements. For example, for a polyurethane foam with a thickness of 2 mm, a lower power (approximately 100 W) and a shorter treatment time (3 minutes) can be used to balance the activation effect and material integrity.

[0024] S2: placing the activated foam substrate and the polyester film in an ultraviolet irradiation device for modification and composite treatment to obtain a composite substrate; In step S2, a polyester film material is selected, preferably polyethylene terephthalate (PET) film, which is suitable as a reinforcing layer for composite material pads due to its good mechanical strength, chemical stability, and transparency. The thickness of the PET film is controlled between 0.1 and 0.2 mm. The PET film is surface-modified and then hot-pressed with an activated foam substrate. During the surface modification stage, an acrylate prepolymer containing a photoinitiator is selected as the modified coating material. This prepolymer can rapidly polymerize under ultraviolet light to form a cross-linked network, thereby improving the surface properties of the PET film. During operation, the acrylate prepolymer is evenly coated on the surface of the PET film, and the coating thickness is controlled to be 5-10 microns to achieve the modification effect while avoiding excessive coating thickness that affects flexibility. Subsequently, the PET film coated with the prepolymer is placed in an ultraviolet irradiation device. The device uses an ultraviolet light source with a wavelength of 365 nanometers. This wavelength can effectively excite the photoinitiator and initiate the free radical polymerization reaction of the prepolymer. The irradiation time is controlled at 2-3 minutes to allow the prepolymer to be completely cross-linked to form a stable network structure. Through this process, a cross-linked coating with high elasticity and adhesive activity is formed on the surface of the PET film, the surface energy is significantly improved, and the contact angle is reduced from the initial 80° to about 50°, indicating that the hydrophilicity and adhesion are significantly improved. After completing the ultraviolet light modification of the PET film, it enters the hot pressing composite stage, and the modified PET film is composited with the activated foam base obtained in step S1 by a hot melt adhesive coating machine. Environmentally friendly polyurethane hot melt adhesive is selected as the adhesive. This adhesive has excellent bonding strength and environmental friendliness. The coating thickness is controlled at 20-30 microns to balance the bonding effect and material cost. The composite process is carried out in a hot melt adhesive coating machine with the equipment temperature set at 120-140°C, the pressure controlled at 0.5-1 MPa, and the composite time at 10-20 seconds to achieve the best bonding effect. The surface of the activated foam substrate in step S1 has been treated with plasma to introduce active groups such as hydroxyl and carboxyl groups. Its surface energy is as high as 50 mN / m or more, forming chemical bonds and physical intercalation with the cross-linked coating on the surface of the modified PET film, thereby significantly improving the interfacial bonding strength. Tests have shown that the peel strength of the composite substrate can reach over 10 N / cm, far exceeding that of unmodified composite materials, demonstrating excellent interfacial stability.

[0025] S3: irradiating the composite substrate row by row along a preset grid pattern with a laser to form a groove network structure on the surface of the composite substrate, thereby obtaining a grid substrate with grid identification lines; In step S3, the composite substrate is placed in a laser engraving machine. A nanosecond pulsed laser with a wavelength of 1064 nanometers is used. This laser, due to its short pulse width and high peak power, is suitable for ablating polymer materials such as PET film with micron-level precision. This laser induces a photothermal or photochemical reaction on the surface, forming the desired groove structure. The laser power ranges from 20 to 30 watts, and the engraving speed is 500 to 1000 mm / s. These parameters require fine-tuning in practice based on the thickness and material properties of the composite substrate. The preset grid pattern consists of 1 mm x 1 mm cells, with a line width of 50 to 100 microns and a groove depth of 10 to 20 microns. This ensures that the grid marking lines are visually distinct while maintaining the overall structural integrity of the composite substrate. This process can be implemented using computer-aided design (CAD) software. The operator enters the preset grid pattern into the system. The laser beam scans the PET film surface line by line according to the programmed instructions, ablating each point in the surface to form a continuous groove network. During the laser engraving process, the high temperature ablation on the PET film surface can trigger oxidation reactions, leading to surface discoloration or the formation of unwanted byproducts, affecting the clarity and aesthetics of the grid marking lines. By introducing nitrogen into the processing area, oxygen is effectively isolated and oxidation is prevented. The nitrogen also acts as a cooling agent, reducing the extent of the heat-affected zone (HAZ), thereby improving the precision and smoothness of the groove edges. For example, in actual production, the nitrogen flow rate is typically controlled at 5-10 liters / minute to balance protection effectiveness and cost. During operation, the composite substrate is fixed to the worktable of the laser engraver, ensuring a flat and wrinkle-free surface to prevent laser focus shift. The laser beam is rapidly deflected by a galvanometer system, scanning the PET film surface line by line along a pre-set path. Each grid line is formed by superimposing laser pulses. After processing, the grid substrate is quality inspected to confirm that the grid cell dimensions, line width, and groove depth meet the design requirements. For example, an optical microscope can be used to measure line widths within the 50-100 micron range, or a surface profilometer can be used to verify that groove depths reach 10-20 microns. If deviations are found, it may be necessary to adjust the laser power or engraving speed and re-process.

[0026] S4: performing a nano-coating spraying treatment on the grid substrate to obtain a coating substrate; In step S4, the mesh substrate is placed in a spray coating system, where a composite solution containing nano-titanium dioxide and a silane coupling agent is applied through a nozzle. The nano-titanium dioxide content in the composite solution is 5-10%, a ratio designed to balance the coating's functionality and cost. Nano-titanium dioxide, due to its photocatalytic properties, decomposes organic pollutants under light, imparting self-cleaning properties to the coating. Its high chemical stability also enhances its antibacterial effect. The silane coupling agent acts as a bridging agent, strengthening the bond between the nano-titanium dioxide particles and the PET film surface, improving the coating's adhesion and durability. The solution's viscosity is controlled between 50 and 100 centipoise. This range ensures uniform coverage of the substrate surface during spraying without causing uneven coating thickness or dripping due to excessive fluidity. The spray coating system utilizes a high-pressure spray system equipped with a precision nozzle to achieve uniform micron-scale coating application. The nozzle pressure is maintained at 0.2 to 0.3 MPa, which produces a fine atomized spray on the substrate surface, resulting in a controlled coating thickness of 5 to 10 microns. In actual operation, the grid substrate is fixed on the workbench of the spraying equipment. The nozzle moves back and forth along the surface of the substrate at a constant speed. The composite solution is sprayed from the nozzle through compressed air or a pumping system and evenly deposited on the surface of the PET film and in the groove network structure. To prevent the coating from clogging the grid marking lines, the spraying angle and distance need to be precisely adjusted. Usually, the distance between the nozzle and the substrate surface is maintained at 15 to 20 cm, and the spraying angle is close to vertical to ensure uniform coverage of the solution without excessive accumulation. Finally, the coating is cured at room temperature for 2 hours. During the curing process, the solvent in the solution gradually evaporates and the coating gradually hardens, forming a protective layer with a hardness of up to 4H.

[0027] S5: performing a hot pressing and shaping process on the coating substrate to obtain a semi-finished gasket product; In step S5, a hot press applies high temperature and high pressure to soften the foam substrate, further fusing it with the PET film and promoting the secondary curing of the nanocoating, resulting in a highly dense and strong semi-finished gasket. The mold surface of the hot press is coated with a non-stick coating, such as polytetrafluoroethylene (PTFE), to prevent the substrate from adhering to the mold under high temperature and pressure, ensuring a smooth and defect-free surface after demolding. This design is crucial for maintaining the clarity of the grid marking lines and the integrity of the coating. During operation, the coated substrate is placed in the working chamber of the hot press, with upper and lower molds corresponding to the upper and lower surfaces of the substrate, respectively. The mold shape and size are pre-customized according to the design requirements of the semi-finished gasket. The hot press temperature is set between 150 and 170 degrees Celsius, a temperature range that softens the foam substrate (polyurethane or polyethylene foam) and activates molecular motion on the surface of the PET film, promoting interfacial bonding between the two without causing overheating and degradation of the material or damage to the nanocoating. The pressure is controlled at 2-3 MPa, so that the substrate is evenly compressed in the mold, eliminating internal pores and improving the density of the material. The holding time is 5-8 minutes. This time range allows the foam substrate and the PET film to fully fuse, while the silane coupling agent and other components in the nano-coating are further cross-linked at high temperature to form a stronger protective layer. During the hot pressing process, the pore structure of the foam substrate is compressed and the thickness is precisely controlled. The reference information mentions that the thickness deviation is controlled at ±0.05 mm, which indicates that the hot pressing molding machine is equipped with a high-precision pressure and displacement control system that can monitor the degree of compression of the substrate in real time. After the hot pressing is completed, the substrate is cooled to near room temperature in the mold to fix its shape, prevent rebound or warping, and transform the coated substrate into a structurally stable gasket semi-finished product.

[0028] S6: Laser cutting the semi-finished gasket according to a preset size to obtain a composite gasket.

[0029] In step S6, before laser cutting, specific preset dimensions must be set. These dimensions can be determined by product design drawings or customer requirements. For example, assume a gasket is used as an internal cushioning component for electronic equipment and needs to be cut into rectangular sheets measuring 100 mm x 50 mm and 2 mm thick, with a tolerance of ±0.1 mm. Laser cutting equipment can be a high-precision CNC laser cutting machine equipped with a high-power laser (such as a CO2 laser or fiber laser) capable of achieving micron-level cutting accuracy. In practice, the semi-finished gasket is secured to the laser cutting machine's worktable using vacuum suction or a clamp to prevent material displacement during cutting. After securing, a preset cutting path is input into the CNC system. This path is generated based on the product design drawings and imported into the machine in a vector file format (such as DXF or G-code). The cutting path includes not only the gasket's outer contour but also any functional internal openings or marking lines. For example, if the gasket requires a hole reserved for mounting in a specific location, the laser cutting machine can complete the cutting of both the outer contour and the inner hole in a single operation, improving production efficiency. The laser power and cutting speed need to be optimized based on the material properties of the semi-finished gasket. For example, a composite gasket may contain a foam substrate, a polyester film, and a nanocoating. These materials have varying thermal sensitivities. Therefore, the laser power (within the range of 50–200 W) and cutting speed (10–100 mm / s) are controlled to avoid overheating that could cause burning of the material or peeling of the coating. If the gasket's foam substrate is sensitive to high temperatures, lower power and faster cutting speeds can be used to minimize the heat-affected zone. After laser cutting, the resulting composite gasket requires subsequent inspection to ensure that product quality meets requirements. The optical inspection system, consisting of a high-resolution CCD camera and image processing software, is used to check the integrity of the gasket's grid markings, coating uniformity, and surface defects. The grid markings are a network of grooves formed by the laser irradiation in step S3. Their integrity directly impacts the gasket's functionality (such as flow guidance and positioning). During inspection, the camera scans the gasket surface, and the software analyzes the continuity and depth of the grid lines. Any broken lines or insufficient depth are considered defective. Furthermore, coating uniformity testing determines the uniformity of the nanocoating by analyzing the intensity distribution of reflected light from the surface. Any areas of missing or accumulated coating are marked as defects. Surface defect testing focuses on minor flaws such as scratches, bubbles, or foreign matter, which may affect the mechanical properties or appearance of the gasket. Through optical inspection, the product qualification rate can reach 99.5%. Rejected products are rejected or reworked. Passing gaskets are vacuum-packed in anti-static PE film to prevent moisture and static damage during transportation, resulting in a composite gasket.

[0030] In one embodiment, the polyester film is a combination of one or more of a PET film, a PBT film, and a PEN film.

[0031] In this embodiment, PET film, PBT film, and PEN film all possess high mechanical strength and chemical stability. PET film (polyethylene terephthalate film) is the preferred material due to its excellent transparency and wide availability. Depending on the specific application requirements, PBT film (polybutylene terephthalate film) and PEN film (polyethylene naphthalate film) can be used as alternative or supplementary options. PBT film, with its high heat resistance and dimensional stability, is suitable for composite gaskets used in high-temperature environments. PEN film, with its excellent weather resistance and barrier properties, is suitable for applications requiring long-term outdoor exposure or requiring special gas barrier properties.

[0032] In one embodiment, the step of subjecting the foam substrate to plasma surface activation treatment to obtain an activated foam substrate comprises: placing the polyurethane foam substrate in an ultrasonic cleaning device, and using a mixed solution of deionized water and isopropyl alcohol as a cleaning medium to clean the polyurethane foam substrate to obtain a foam substrate; The foam substrate is placed in a low-pressure plasma treatment chamber, and a mixed gas of argon and nitrogen is introduced, with the volume ratio of argon to nitrogen controlled to be 3:1 and the power set to 200 W to obtain a primary activated substrate; The gas was exhausted and a mixed gas of oxygen and carbon tetrafluoride was introduced, the volume ratio of oxygen to carbon tetrafluoride was controlled to be 4:1, and the power was set to change periodically between 250W and 350W to obtain an activated foam base.

[0033] In the above embodiment, a polyurethane foam substrate was placed in an ultrasonic cleaning apparatus using a mixture of deionized water and isopropyl alcohol as the cleaning medium. Deionized water effectively removes water-soluble impurities, while isopropyl alcohol helps dissolve organic contaminants such as grease or processing residues. Assuming a 2:1 volume ratio of deionized water to isopropyl alcohol in the cleaning solution, the ultrasonic equipment frequency was set to 40 kHz, the power was 300 W, and the cleaning time was controlled to be 5-10 minutes. During the cleaning process, the ultrasound-induced cavitation effect causes microbubbles in the solution to rapidly expand and collapse, generating localized high pressure and microjets, which thoroughly remove particles and dirt from the foam surface. After cleaning, the foam substrate was dried with nitrogen in a clean environment to prevent secondary contamination and then dried in a drying oven at 50°C for 30 minutes to remove any residual moisture from the surface. After cleaning and drying, the foam substrate entered a plasma surface activation treatment, which involved placing the foam substrate in a low-pressure plasma treatment chamber. This chamber was a vacuum environment with a pressure controlled at 0.1-1 Pa to ensure efficient ionization of gas molecules and stable plasma generation. A mixture of argon and nitrogen at a volume ratio of 3:1 is introduced into the chamber. Argon, as an inert gas, generates a stable plasma, while nitrogen helps introduce nitrogen-containing functional groups (such as amino groups) onto the foam surface, thereby increasing its hydrophilicity and chemical activity. The plasma treatment power is set at 200W, and the treatment time is 3-5 minutes. During this process, high-energy particles in the plasma bombard the foam surface, breaking surface molecular bonds and forming free radicals and active sites. This also removes residual organic contaminants, resulting in a primary activated substrate. Next, the chamber is vented and replaced with a mixture of oxygen and carbon tetrafluoride at a volume ratio of 4:1. The power is set to cycle between 250W and 350W. This stage aims to introduce oxygen-containing functional groups (such as hydroxyl and carboxyl groups) through the oxygen plasma, further improving surface polarity and adhesion. The carbon tetrafluoride plasma also deposits a thin fluorinated layer on the surface, enhancing chemical resistance and hydrophobicity. Periodic power changes mean that the power is switched between 250W (low power stage, focusing on the introduction of functional groups) and 350W (high power stage, focusing on the deposition of the fluoride layer) in a cycle of 30 seconds. The total processing time is 5 to 7 minutes. Dynamic power adjustment can balance the effects of surface activation and fluorination modification, avoiding excessive etching or uneven coating problems that may occur under a single power.

[0034] In one embodiment, the step of placing the activated foam substrate and the polyester film in an ultraviolet irradiation device for modification and composite treatment to obtain a composite substrate includes: A mixed solution of acrylate prepolymer containing a photoinitiator and nano zinc oxide particles in propylene is coated on the surface of the polyester film, and pre-cured under the protection of an inert gas to obtain an initial polyester film; The initial polyester film is placed in an ultraviolet irradiation device for modification treatment, the ultraviolet light source of the device is set to have a wavelength of 355-365 nm and an irradiation intensity of 100-150 mW / cm², to obtain a modified polyester film; Applying an environmentally friendly polyurethane hot melt adhesive on the surface of the activated foam base, and flattening the surface with a cooling roller to obtain an adhesive foam base; The modified polyester film and the adhesive foam substrate are subjected to hot melt lamination treatment at a lamination temperature of 120-140° C. and a lamination time of 30-60 seconds to form a composite substrate.

[0035] In the above embodiment, a polypropylene mixed solution of an acrylate prepolymer containing a photoinitiator and nano-zinc oxide particles is coated on the surface of a polyester film. The acrylate prepolymer rapidly crosslinks and cures under UV light, forming a highly tough coating. The nano-zinc oxide particles enhance the coating's mechanical strength and impart antibacterial and UV-shielding properties. The formulation of the polypropylene mixed solution can be: 60 wt% acrylate prepolymer, 2 wt% photoinitiator (such as benzophenone), 5 wt% nano-zinc oxide (particle size 20-50 nm), and the remainder solvent (such as ethyl acetate). Coating is performed using precision doctor blade equipment, with a coating thickness controlled to 10-15 μm. Precuring is then performed under a nitrogen-protected inert atmosphere. Precuring involves irradiating the coating with low-intensity UV light (wavelength 365 nm, intensity 50 mW / cm²) for 30 seconds to partially crosslink the coating surface, forming an initial polyester film and preventing the coating from flowing or sticking during subsequent processing. The nitrogen atmosphere prevents oxygen from inhibiting free radical polymerization, thereby improving precuring efficiency. The initial polyester film is subjected to a modification treatment in an ultraviolet irradiation device using a UV light source with a wavelength of 355-365 nm, an irradiation intensity of 100-150 mW / cm², and a treatment time of 60-90 seconds. The high-intensity UV light initiates deep crosslinking of the acrylate coating. Simultaneously, the nano-zinc oxide particles, under UV excitation, produce a photocatalytic effect, generating reactive oxygen species that further modify the polyester film surface, enhancing its surface polarity and its bonding with the adhesive layer. In another embodiment, helium and a small amount of vinyltrimethoxysilane (10:1 by volume) can be introduced at a pressure of 0.5 Pa and a power of 50 W for 2 minutes. Under the action of the plasma, the vinyltrimethoxysilane decomposes and deposits on the film surface, forming a nano-coating containing silicone and vinyl groups. This increases surface activity, provides additional chemical bonding sites for subsequent hot-melt lamination, and significantly enhances the interlayer bonding strength of the composite substrate. An environmentally friendly polyurethane hot-melt adhesive is evenly applied to the surface of an activated foam substrate, with a coating thickness of 20-30 μm. A hot-melt adhesive spraying device is used to ensure a uniform, bubble-free adhesive layer. After application, the foam substrate is flattened by passing it over a cooling roller (15-20°C) for approximately 10 seconds to stabilize the adhesive layer and prevent the adhesive from penetrating the foam pores, resulting in a bonded foam substrate. Prior to hot-melt adhesive application, the activated foam substrate is placed in a microwave treatment device set at a microwave frequency of 2.45 GHz, a power of 100 W, and a treatment time of 20 seconds under a low-pressure helium atmosphere (0.2 Pa). Microwave treatment selectively heats activated functional groups (such as hydroxyl and amino groups) on the foam surface, increasing their chemical activity. It also subtly alters the surface microstructure, increasing porosity and roughness, thereby enhancing the permeability and adhesion of the hot-melt adhesive. Subsequently, the modified polyester film and the adhesive foam base enter the hot melt composite treatment stage. The composite temperature is controlled at 120-140°C, the composite time is 30-60 seconds, and a hot press composite machine is used to make the pressure uniform (about 0.5MPa).During this process, the polyurethane hot melt adhesive softens at high temperature and penetrates into the surface coating of the modified polyester film, forming chemical bonds and physical intercalation with the silicone and vinyl coatings, ultimately forming a high-strength composite substrate.

[0036] In one embodiment, the step of irradiating the composite substrate line by line along a preset grid pattern with a laser to form a groove network structure on the surface of the composite substrate to obtain a grid substrate with grid identification lines includes: Collecting first surface topography data of the composite substrate using a computer device, and generating a laser irradiation path based on the first surface topography data, wherein the laser irradiation path includes intersecting lines in different directions and a varying area of a preset depth; performing incident irradiation treatment on the composite substrate at multiple angles according to the laser irradiation path to form a primary network substrate, wherein the intersection of the multiple angles forms a varying region of the preset depth; collecting second surface topography data of the primary network substrate, and optimizing the curvature of the intersection according to the second surface topography data to form an optimized curvature parameter; performing a secondary laser irradiation process on the primary network substrate according to the optimized curvature parameters to form an optimized network substrate; The inner wall of the groove on the optimized network substrate is etched based on a laser, and the edge of the inner wall of the groove is locally melted to obtain a grid substrate with grid identification lines.

[0037] In this embodiment, computer equipment collects first surface topography data of the composite substrate. Specifically, a high-resolution 3D laser scanner (with a resolution of up to 0.1 μm) is used to perform a panoramic scan of the composite substrate surface, acquiring 3D topography data including surface roughness, microscopic defects, and material distribution malformations. Based on this data, the computer generates a laser irradiation path using a specialized algorithm (such as a path optimization algorithm based on Delaunay triangulation). The path design includes intersecting lines along the X and Y axes, with depth variations (e.g., from 50 μm to 100 μm) at the intersections to form a functionally graded grid structure. Following the generated laser irradiation path, a femtosecond laser (1030 nm wavelength, 500 fs pulse width, 100 kHz repetition rate) is used to irradiate the composite substrate line by line at multiple incident angles (e.g., 0°, 45°, and 90°) to form a primary network substrate. The ultrashort pulse characteristics of the femtosecond laser enable non-thermal processing, minimizing damage to the composite substrate from heat-affected zones. During the irradiation process, the laser power was controlled between 0.5 and 1 W, and the scanning speed was 500 mm / s. At the intersection, the laser pulse energy was dynamically modulated (for example, by increasing the energy by 20%) to create a variable region of predetermined depth, with a depth error controlled within ±5 μm. After the primary irradiation, the adaptive light field-based micro-nanostructuring step was performed. Specifically, the composite substrate was placed in a light field system controlled by a spatial light modulator (SLM). The SLM generated a customized Bessel beam, which was focused on the intersection region, inducing the formation of periodic nanoscale stripes (with a period of approximately 200 nm). These nanostripes were embedded in the groove surface through photoinduced plasmon effects, enhancing the surface functionality of the mesh structure (such as hydrophobicity or optical scattering). Secondary surface topography data of the primary network substrate was collected, and a 3D laser scanner was used to analyze the curvature distribution at the intersection and the topographic deviation of the groove edges. Based on this data, finite element simulation and curvature optimization algorithms (such as a B-spline-based curvature smoothing algorithm) were used to calculate and optimize the curvature parameters, ensuring a smooth geometric transition at the intersection with a curvature radius error within ±2 μm. The optimized curvature parameters are used to guide secondary laser irradiation, and a laser (wavelength 532nm, pulse width 10ps, power 0.3W) is used to fine-tune the primary network substrate, and the scanning speed is reduced to 200mm / s to improve precision. The secondary irradiation not only repairs minor defects in the primary processing (such as edge burrs), but also further optimizes the geometric consistency of the groove by precisely controlling the laser focal trajectory to form an optimized network substrate. Finally, the inner wall of the groove of the optimized network substrate is etched based on the laser. An excimer laser (wavelength 248nm, pulse width 20ns, power 0.2W) is used to remove tiny residues on the inner wall of the groove with high precision etching. At the same time, the edge of the groove is locally melted by adjusting the laser pulse frequency (50Hz) to form a smooth edge transition, and the edge roughness Ra is controlled below 0.5μm.After etching, the microstructure is enhanced using laser multiphoton polymerization. Specifically, the optimized network substrate is placed in a liquid precursor containing a photosensitive monomer (such as an acrylate monomer) and a photoinitiator. A laser (wavelength 780nm, pulse width 100fs, power 10mW) is scanned along the inner wall of the grooves, inducing the photosensitive monomer to polymerize locally on the inner wall of the grooves to form a three-dimensional microporous structure (pore size approximately 1μm). These microporous structures not only increase the surface area of the grooves, enhancing the adhesion of subsequent coatings or filling materials, but also serve as microfluidic channels or catalyst carriers, increasing the functional diversity of the grid substrate. Notably, the identification lines are the linear components of the groove network structure formed by laser processing on the surface of the composite substrate. These lines form the grid pattern on the grid substrate. The grid identification lines are a specific manifestation of the groove network structure, appearing as linear grooves of a certain width and depth extending along the X and Y axes (or other predetermined directions). These lines are formed according to a computer-generated laser irradiation path, which includes intersecting lines in different directions (for example, horizontal and vertical lines intersecting to form a grid). The intersections also have preset depth variations (for example, the depth gradually changes from 50μm to 100μm). The depth variation of the intersections eliminates the concentration of stress at a single point and evenly distributes it, thereby improving the compressive strength, toughness, and overall mechanical stability of the composite substrate. In printed underlay applications, the structure of the grid identification lines provides a specific patterned surface. The grooves formed by these identification lines and the variation of the intersections can improve adhesion and printing precision during the printing process. The special design of the grid pattern can ensure that the printed coating is evenly distributed on the underlay surface, while strengthening the adhesion between the coating and the underlay substrate, improving the quality and stability of the final printed product.

[0038] In another embodiment, the computer device calculates the optimized curvature by the following expression: ;in, is the optimized curvature parameter, which represents the target curvature value at the intersection (unit: 1 / μm); κ(s) is the local curvature at a point ss along the path ΓΓ, reflecting the curvature distribution at the intersection of the primary network substrate and calculated from the secondary surface topography data; The reference curvature value is used as the target benchmark for curvature optimization to measure the deviation between the actual curvature and the ideal curvature; is the second-order Laplace operator of the local curvature κ(s), which characterizes the spatial rate of change of curvature and is used to smooth the curvature distribution and reduce local mutations (such as edge burrs); is the stress distribution at a point s along the path Γ calculated by finite element simulation, reflecting the mechanical stress concentration at the intersection; , , is the weight coefficient, corresponding to the contribution of the curvature smoothing term, curvature deviation term, and stress optimization term, respectively, balancing the influence of the three terms in the formula; Γ is the curvature optimization path in the intersection area, usually a closed curve along the edge of the groove; s is the arc length parameter on the path Γ, which characterizes the position along the path and is used to parameterize the curvature and stress distribution; T(s) is the tangent vector at a point s on the path Γ (, describing the geometric direction of the path, used to regularize the denominator and enhance the stability of the curvature optimization; λ is the normalization coefficient (unit: none), which controls the influence of the tangent vector term to prevent the denominator from being too small or the calculation from being unstable; is the line integral along the path Γ, which integrates the curvature, stress and tangent vector information into the global optimization result based on the arc length s; It is the square of the deviation between the actual curvature and the reference curvature, which quantifies the curvature deviation. The optimization goal is to make the actual curvature close to the reference curvature. It is the square of the tangent vector modulus, which enhances the geometric stability of the denominator and avoids numerical errors caused by sudden changes in path direction.

[0039] In one embodiment, the step of performing a secondary laser irradiation treatment on the primary network substrate according to the optimized curvature parameters to form an optimized network substrate includes: Dividing the surface of the primary network substrate into a plurality of energy partitions according to the second surface topography data of the primary network substrate and the optimized curvature parameter; A corresponding laser power is set for each of the energy partitions, and the primary network substrate is irradiated according to the laser power to obtain the optimized network substrate.

[0040] In this embodiment, the second surface topography data of the primary network substrate is obtained. The topography data obtained by microscopy or laser confocal scanning technology can characterize the microscopic features of the substrate surface in detail, including surface roughness, curvature changes, and structural discontinuities. The unique energy input required for different areas of the substrate surface is identified through a partitioning strategy, and the curvature parameters are integrated with the topography data to generate a three-dimensional energy partition map. This partition map divides the substrate surface into multiple discrete areas, each with a unique curvature profile and material properties, such as local density or thermal conductivity, or directly uses groove depth and width as the partition basis. Different laser power settings are used for different energy partitions so that each area receives the laser energy that best suits its surface characteristics. Specifically, for example, for areas with larger curvature or higher surface roughness, the laser power is appropriately reduced to reduce the heat-affected zone and surface damage, maintaining the integrity and functionality of the material. For areas with smaller curvature or smoother surfaces, the laser power can be appropriately increased to ensure sufficient energy input and achieve precise structural modification. By precisely controlling the laser power in each energy zone, not only is the geometry and curvature of the intersections optimized, but material loss due to over-processing is also reduced, improving processing efficiency and the overall performance of the composite substrate. After the secondary laser irradiation treatment, the resulting optimized network substrate exhibits a more uniform and refined grid structure, with smooth grooves and natural edge transitions, demonstrating excellent surface quality and mechanical strength, and enhancing the compressive strength and toughness of the grid substrate.

[0041] In one embodiment, the step of spraying the mesh substrate with a nano-coating to obtain a coated substrate comprises: Spraying a composite solution containing nano-titanium dioxide, a silane coupling agent, and a polyurethane resin onto the surface of the mesh substrate to form a primary-coated mesh substrate, wherein, calculated by mass ratio, titanium dioxide accounts for 6-8%, the silane coupling agent accounts for 2-3%, and the remainder is the polyurethane resin; The pre-coated mesh substrate is placed in a reaction kettle and cured at a low temperature of 50-60° C. for 1.5-2 hours to obtain a cured mesh substrate; A polishing liquid containing nano-alumina particles is applied to the surface of the solidified grid substrate, and the solidified grid substrate coated with the polishing liquid is polished using a polishing device to obtain a coated substrate, wherein the alumina particles have a size of 50-80 nm and the polishing pressure is 0.1-0.15 MPa.

[0042] In this embodiment, the surface of the mesh substrate is subjected to a nano-coating spray treatment, and a composite solution needs to be prepared. The composite solution consists of nano-titanium dioxide, a silane coupling agent, and a polyurethane resin, wherein the mass proportion of titanium dioxide is controlled to be 6-8%, the silane coupling agent accounts for 2-3%, and the rest is polyurethane resin. Nano-titanium dioxide can significantly enhance the antibacterial and self-cleaning properties of the coating due to its high catalytic activity and photochemical stability, while the silane coupling agent promotes the chemical bonding between the nanoparticles and the polyurethane resin through the active groups in its molecular structure, thereby improving the adhesion and stability of the coating. The polyurethane resin, as a matrix material, gives the coating excellent flexibility and weather resistance. In order to achieve the best spraying effect, the spraying process needs to be carried out in a dust-free environment, using high-voltage electrostatic spraying equipment, the spraying pressure is controlled at 0.2-0.3 MPa, the distance between the nozzle and the substrate surface is maintained at 15-20 cm, and the spraying speed is 0.5-0.8 m / s to form a uniform thickness of the initial coating mesh substrate. After spraying, the pre-coated mesh substrate is placed in a reactor for low-temperature curing at 50-60°C for 1.5-2 hours. During the curing process, an inert gas mixture containing trace amounts of ozone (ozone concentration of 0.01-0.02%) can be introduced into the reactor. Ozone, as a strong oxidant, can induce a mild oxidation reaction on the surface molecules of the coating at low temperatures, thereby promoting interfacial bonding between the polyurethane resin and the nano-titanium dioxide. After curing, the polishing stage begins. The polishing slurry contains nano-alumina particles with a size of 50-80 nm, and the polishing pressure is controlled at 0.1-0.15 MPa. The nano-alumina particles effectively remove micro-protrusions and defects on the cured coating surface. The polishing equipment uses a high-precision chemical mechanical polishing (CMP) system, with a polishing disk speed of 50-80 rpm and a polishing slurry flow rate of 100-150 mL / min. In order to ensure the uniformity of the polishing process, the contact angle between the polishing head and the substrate surface is controlled at 5~10°. 0.5~1% fluorinated silane modifier can also be added to the polishing liquid to form a super hydrophobic film on the coating surface. The resulting coating substrate reduces the friction coefficient of the coating surface and significantly improves its anti-fouling ability and chemical corrosion resistance, making the coating substrate perform better in harsh environments.

[0043] In one embodiment, the step of performing a hot pressing and shaping treatment on the coated substrate to obtain a semi-finished gasket product includes: placing the coating substrate in a reaction kettle, and performing a preheating softening treatment on the coating substrate at a temperature of 120-130° C. to obtain a preheated substrate; spraying a fluorinated non-stick coating onto the surface of a pre-shaping mold, placing the preheated substrate in the pre-shaping mold, and performing a pre-shaping treatment on the preheated substrate at 0.5-1 MPa to obtain a pre-shaping substrate; Transferring the pre-shaped substrate to a high-temperature and high-pressure hot press for high-temperature and high-pressure shaping treatment to obtain a shaped substrate, wherein the hot pressing temperature is set at 160-180° C. and the pressure is set at 2.5-3.5 MPa; The shaped substrate is subjected to a gradient cooling treatment, in the first stage, the temperature is reduced from 180°C to 100°C, and the cooling rate is controlled at 5°C / min. In the second stage, the temperature is reduced from 100°C to 50°C, and the cooling rate is slowed down to 3°C / min to obtain a semi-finished gasket.

[0044] In this example, the coated substrate is preheated and softened in a reactor at a temperature controlled between 120°C and 130°C to achieve appropriate flexibility and plasticity. During the preheating process, an inert gas mixture containing trace amounts of amino-functionalized gas (amino gas concentration of 0.05-0.1%) is introduced into the reactor. At high temperatures, this gas undergoes a mild chemical reaction with active sites on the coated substrate surface, forming trace amino functional groups. This improves the interfacial bonding ability of the substrate surface and provides a better molecular-level adhesion foundation for subsequent pre-shaping and hot-pressing. After pre-shaping, low-pressure shaping is performed to lay the foundation for subsequent high-temperature and high-pressure shaping. The pre-shaping mold surface is sprayed with a fluorinated non-stick coating to prevent the substrate from adhering to the mold surface during the shaping process and reduce demolding resistance. The fluorinated non-stick coating is applied using plasma-enhanced chemical vapor deposition (PECVD) technology, with a coating thickness of 0.5-1 μm to ensure a balanced non-stick performance and mold surface wear resistance. The preheated substrate is then placed in a pre-shaping mold and pre-shaped at a pressure of 0.5-1 MPa. The mold temperature is set at 80-90°C for 3-5 minutes. After that, the substrate is transferred to a high-temperature, high-pressure hot press for high-temperature, high-pressure shaping. The hot-pressing temperature is set at 160-180°C, the pressure is 2.5-3.5 MPa, and the hot-pressing time is 10-15 minutes. The high temperature and high pressure further crosslink and solidify the polymer molecular chains within the substrate, while also optimizing the interfacial bonding strength between the coating and the substrate. A gradual loading strategy is used to apply pressure to avoid microcracks in the substrate caused by transient high pressure. After hot-pressing, the shaped substrate undergoes a gradient cooling process to eliminate thermal stresses and maintain dimensional stability. The first stage is from 180°C to 100°C at a cooling rate of 5°C / min. The second stage is from 100°C to 50°C, with the cooling rate slowed to 3°C / min. The cooling process uses programmed cooling equipment to achieve a smooth temperature transition by precisely controlling the flow rate and temperature of the cooling medium (nitrogen or air) to obtain a semi-finished gasket product.

[0045] In one embodiment, the step of laser cutting the semi-finished gasket according to a preset size to obtain a composite gasket includes: Laser cutting the semi-finished gasket product according to a preset profile using a multi-wavelength laser to obtain a cut substrate, wherein the short-wavelength laser corresponds to the polyester film layer and the long-wavelength laser corresponds to the foam base; Obtaining the integrity of the marking line on the surface of the cut substrate using an optical inspection device, and determining whether the cut substrate meets the preset size requirements; If not, the cut substrate is corrected until it meets the preset size requirements to obtain a composite material liner.

[0046] In this embodiment, multi-wavelength lasers are used for layered cutting. A short-wavelength laser (e.g., ultraviolet laser, wavelength approximately 355 nanometers) is used to cut the polyester film layer. Its high energy density enables precise edge processing and prevents scorching or deformation of the material due to thermal effects. A long-wavelength laser (e.g., infrared laser, wavelength approximately 1064 nanometers) is used to cut the foam substrate. Its lower energy density effectively penetrates the porous structure while minimizing thermal damage to the substrate. To improve cutting accuracy, in practice, a cutting profile can be generated using computer-aided design (CAD) software and imported into the laser control system. During the cutting process, the laser dynamically adjusts its focus and power based on this profile data to accommodate changes in material thickness and density. After the initial cut, the integrity of the marking line on the cut substrate surface is determined using optical inspection equipment. The optical inspection equipment can include a high-resolution CCD camera and accompanying image processing software to capture the marking line on the cut substrate surface, obtain the marking line's continuity and width data, and then analyze the marking line's integrity and deviation from the preset profile using image processing algorithms (e.g., edge detection and geometric fitting). If the marking line is found to be broken or offset, it indicates that there may be problems such as uneven laser power or material positioning deviation during the cutting process. When the test results show that the cut substrate does not meet the preset size requirements, the cut substrate is corrected until it meets the preset size requirements. The correction can include two aspects: one is secondary laser cutting for size deviation, and the other is optimization of edge quality. In the secondary cutting, the laser parameters are readjusted according to the test feedback data, such as reducing the power to reduce the heat-affected zone, or adjusting the cutting speed to improve accuracy. In another embodiment, after the cutting and correction are completed, the composite material liner is subjected to surface functionalization treatment and performance verification testing. The surface functionalization treatment is intended to improve the application performance of the liner. Through plasma treatment technology, specific chemical groups (such as hydroxyl or amino groups) are introduced to the surface of the liner to enhance its adhesion or water resistance. The treatment is carried out in a vacuum environment. By controlling the energy and gas composition of the plasma, it is ensured that the functionalization effect is uniform and does not damage the material structure. Performance verification tests include a series of assessments on the mechanical properties and environmental adaptability of the liner, such as testing the compression rebound performance of the liner using a dynamic mechanical analyzer (DMA), or simulating extreme environments through a constant temperature and humidity chamber to verify its dimensional stability and durability, thereby obtaining a composite material liner.

[0047] It is worth noting that all the equipment described in this application is achievable using existing technologies, the algorithms described are based on mature existing technologies, and the chemicals and conditions used in the preparation process are within safe ranges and pose no risk to operators or the environment. Furthermore, the prepared composite gasket exhibits excellent thermal conductivity and self-healing capabilities, demonstrating good reliability and stability.

[0048] The present invention also discloses a composite material liner, which is made by a production process of a composite material liner as described in any one of the above items, and includes a polyester film layer, a foam base, and a grid structure arranged between the polyester film layer and the foam base, wherein the grid structure is composed of an optimized network substrate, the surface of the network substrate is covered with a nano-coating, and nano-titanium dioxide particles are evenly dispersed in the nano-coating, giving the liner excellent antibacterial and self-cleaning properties. The polyester film layer serves as the outer surface layer of the liner, providing good wear resistance and chemical stability, and can effectively resist erosion from the external environment; the foam base gives the liner excellent cushioning and sound absorption properties, so that the liner can provide good comfort and sound insulation during use. It also includes an identification line, which is provided on the semi-finished liner to indicate the cutting path and size positioning.

[0049] As described above, the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application has been described in detail with reference to the above embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the above embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present application.

Claims

1. A production process for a composite material liner, characterized in that: include: performing plasma surface activation treatment on the foam substrate to obtain an activated foam substrate; placing the activated foam substrate and the polyester film in an ultraviolet irradiation device for modification and composite treatment to obtain a composite substrate; Based on the laser irradiation on the composite substrate line by line along a preset grid pattern, a groove network structure is formed on the surface of the composite substrate to obtain a grid substrate with grid identification lines; performing nano-coating spraying treatment on the grid substrate to obtain a coating substrate; Performing hot pressing and shaping treatment on the coating substrate to obtain a semi-finished gasket product; The semi-finished gasket is laser cut according to a preset size to obtain a composite gasket.

2. The production process of a composite material liner according to claim 1, characterized in that: The polyester film is a combination of one or more of a PET film, a PBT film and a PEN film.

3. The production process of a composite material liner according to claim 1, characterized in that: The step of subjecting the foam substrate to plasma surface activation treatment to obtain an activated foam substrate comprises: placing the polyurethane foam substrate in an ultrasonic cleaning device, and using a mixed solution of deionized water and isopropyl alcohol as a cleaning medium to clean the polyurethane foam substrate to obtain a foam substrate; The foam substrate is placed in a low-pressure plasma treatment chamber, and a mixed gas of argon and nitrogen is introduced, with the volume ratio of argon to nitrogen controlled to be 3:1 and the power set to 200 W to obtain a primary activated substrate; The gas was exhausted and a mixed gas of oxygen and carbon tetrafluoride was introduced, the volume ratio of oxygen to carbon tetrafluoride was controlled to be 4:1, and the power was set to change periodically between 250W and 350W to obtain an activated foam base.

4. The production process of a composite material liner according to claim 1, characterized in that: The step of placing the activated foam substrate and the polyester film in an ultraviolet irradiation device for modification and composite treatment to obtain a composite substrate comprises: A mixed solution of acrylate prepolymer containing a photoinitiator and nano zinc oxide particles in propylene is coated on the surface of the polyester film, and pre-cured under the protection of an inert gas to obtain an initial polyester film; The initial polyester film is placed in an ultraviolet irradiation device for modification treatment, the ultraviolet light source of the device is set to have a wavelength of 355-365 nm and an irradiation intensity of 100-150 mW / cm², to obtain a modified polyester film; Applying an environmentally friendly polyurethane hot melt adhesive on the surface of the activated foam base, and flattening the surface with a cooling roller to obtain an adhesive foam base; The modified polyester film and the adhesive foam substrate are subjected to hot melt lamination treatment at a lamination temperature of 120-140° C. and a lamination time of 30-60 seconds to form a composite substrate.

5. The production process of a composite material liner according to claim 1, characterized in that: The step of irradiating the composite substrate line by line along a preset grid pattern with a laser to form a groove network structure on the surface of the composite substrate to obtain a grid substrate with grid identification lines includes: Collecting first surface topography data of the composite substrate using a computer device, and generating a laser irradiation path based on the first surface topography data, wherein the laser irradiation path includes intersecting lines in different directions and a varying area of a preset depth; performing incident irradiation treatment on the composite substrate at multiple angles according to the laser irradiation path to form a primary network substrate, wherein the intersection of the multiple angles forms a varying region of the preset depth; collecting second surface topography data of the primary network substrate, and optimizing the curvature of the intersection according to the second surface topography data to form an optimized curvature parameter; performing a secondary laser irradiation process on the primary network substrate according to the optimized curvature parameters to form an optimized network substrate; The inner wall of the groove on the optimized network substrate is etched based on a laser, and the edge of the inner wall of the groove is locally melted to obtain a grid substrate with grid identification lines.

6. The production process of a composite material liner according to claim 5, characterized in that: The step of performing a secondary laser irradiation treatment on the primary network substrate according to the optimized curvature parameters to form an optimized network substrate comprises: Dividing the surface of the primary network substrate into a plurality of energy partitions according to the second surface topography data of the primary network substrate and the optimized curvature parameter; A corresponding laser power is set for each of the energy partitions, and the primary network substrate is irradiated according to the laser power to obtain the optimized network substrate.

7. The production process of a composite material liner according to claim 1, characterized in that: The step of spraying the mesh substrate with a nano-coating to obtain a coated substrate comprises: Spraying a composite solution containing nano-titanium dioxide, a silane coupling agent, and a polyurethane resin onto the surface of the mesh substrate to form a primary-coated mesh substrate, wherein, calculated by mass ratio, titanium dioxide accounts for 6-8%, the silane coupling agent accounts for 2-3%, and the remainder is the polyurethane resin; The pre-coated mesh substrate is placed in a reaction kettle and cured at a low temperature of 50-60° C. for 1.5-2 hours to obtain a cured mesh substrate; A polishing liquid containing nano-alumina particles is applied to the surface of the solidified grid substrate, and the solidified grid substrate coated with the polishing liquid is polished using a polishing device to obtain a coated substrate, wherein the alumina particles have a size of 50-80 nm and the polishing pressure is 0.1-0.15 MPa.

8. The production process of a composite material liner according to claim 1, characterized in that: The step of performing hot pressing and shaping treatment on the coating substrate to obtain a semi-finished gasket product comprises: placing the coating substrate in a reaction kettle, and performing a preheating softening treatment on the coating substrate at a temperature of 120-130° C. to obtain a preheated substrate; spraying a fluorinated non-stick coating onto the surface of a pre-shaping mold, placing the preheated substrate in the pre-shaping mold, and performing a pre-shaping treatment on the preheated substrate at 0.5-1 MPa to obtain a pre-shaping substrate; Transferring the pre-shaped substrate to a high-temperature and high-pressure hot press for high-temperature and high-pressure shaping treatment to obtain a shaped substrate, wherein the hot pressing temperature is set at 160-180° C. and the pressure is set at 2.5-3.5 MPa; The shaped substrate is subjected to a gradient cooling treatment, in the first stage, the temperature is reduced from 180°C to 100°C, and the cooling rate is controlled at 5°C / min. In the second stage, the temperature is reduced from 100°C to 50°C, and the cooling rate is slowed down to 3°C / min to obtain a semi-finished gasket.

9. The production process of a composite material liner according to claim 1, characterized in that: The step of laser cutting the semi-finished gasket according to a preset size to obtain a composite gasket includes: Laser cutting the semi-finished gasket product according to a preset profile using a multi-wavelength laser to obtain a cut substrate, wherein the short-wavelength laser corresponds to the polyester film layer and the long-wavelength laser corresponds to the foam base; Obtaining the integrity of the marking line on the surface of the cut substrate using an optical inspection device, and determining whether the cut substrate meets the preset size requirements; If not, the cut substrate is corrected until it meets the preset size requirements to obtain a composite material liner.

10. A composite material liner, characterized in that: The composite material liner is produced by the production process of any one of claims 1 to 9.

Citation Information

Patent Citations

  • Method for improving bonding strength of coating

    CN106676449A

  • Method for improving bonding performance of composite film

    CN108189525A

  • Super-hydrophobic fabric and preparation method thereof

    CN115262211A

  • Recessed contour edge path planning algorithm based on laser scanning

    CN116797616A

  • Optical element polishing white pad with high removal rate and production process thereof

    CN118528122A

Cited By

  • Preparation method of reticulated protective film

    CN121131209A